Developmental activities and the acquisition of superior anticipation and decision making in soccer players - Roca, A.; Williams, A. M.; Ford, P. R. (Journal of Sports Sciences, 2012)
We examined whether soccer players with varying levels of perceptual-cognitive expertise can be differentiated based on their engagement in various types and amounts of activity during their development. A total of 64 participants interacted with life-size video clips of 11 versus 11 dynamic situations in soccer, viewed from the first-person perspective of a central defender. They were required to anticipate the actions of their opponents and to make appropriate decisions as to how best to respond. Response accuracy scores were used to categorise elite players (n=48) as high- (n=16) and low-performing (n=16) participants. A group of recreational players (n=16) who had lower response accuracy scores compared to the elite groups acted as controls. The participation history profiles of players were recorded using retrospective recall questionnaires. The average hours accumulated per year during childhood in soccer-specific play activity was the strongest predictor of perceptual-cognitive expertise. Soccer-specific practice activity during adolescence was also a predictor, albeit its impact was relatively modest. No differences were reported across groups for number of other sports engaged in during development, or for some of the key milestones achieved. A number of implications for talent development are discussed.